Brill's companion to classics and early anthropology - Varto, Emily. (Brill's Companions to Classical Reception, 2018)
The chapters in Brill's Companion to Classics and Early Anthropology explore key points of interaction between classics and anthropology from the eighteenth to the mid-twentieth century. Ancient Greece and Rome played varying roles in early anthropological thinking, from the observations of colonial officials and missionaries, through the ethnography and evolutionary ethnology of the late nineteenth century, and into the professionalized social sciences of the twentieth century. The chapters illuminate these roles and uncover an intellectual history of fission and fusion, exposing common interests and opposing methodologies, shared theories and conflicting datasets, close collaborations and adversarial estrangements. In augmenting and reevaluating this history, the volume offers a new and nuanced picture of the early formative relationship between the two disciplines.